Penerapan Model TGT (Team Game Tournament) menggunakan Media Audio terhadap Hasil Belajar pada Pembelajaran Fabel MTs. S Sabbangparu - Muhlis, Muhlis; Ebe, Hj. Andi; Samad, Ahmad Ghazali; Hasri, Ahmad Fudhayl; Nurcaya, Nurcaya (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
One of the learning models that can be used in learning Indonesian is TGT (Team Game Tournament), especially about fables so that student involvement can be optimal which has an impact on the acquisition of learning outcomes. Therefore, this study aims to describe the results in learning fables in class VII.3 MTs. S Sabbangparu after using audio media and TGT learning model. The method used in this research is class action research (PTK), the research subjects totaled 15 people. The instruments used for data collection were tests and non-tests. Data analysis techniques were carried out quantitatively and qualitatively. The results showed that the learning of fable text with the average score of all groups was 71 in cycle I and became 93 in cycle II, the results of cycle I on the percentage of student completeness were 33.3% to 100% in cycle II and out of 15 students 9 (60%) felt very happy in learning fable TGT model using audio media and 6 students (40%) felt ordinary. This is evidence of success in the use of audio media through the TGT model in fable learning class VII.3 MTs S Sabbangparu.